Suitable site Selection for Maize Cultivation Based on the crop of Temperature Supply Needs in Northwestern Iran - zeinab ebrahimighalelani; javad khoshhal dastjerdi; hojatolah yazdanpanah (تحقیقات کاربردی علوم جغرافیایی)
Each plant needs a certain amount of heat at the time of planting and during its growth and development. The purpose of this research is to determine the thermal requirements of grain corn in the stages of growth phenology in the climatic conditions of Moghan and to determine the suitable cultivation areas in terms of heat requirements in northwest Iran. For this purpose, the technology of corn variety Single Cross 704 recorded consecutively from 2011 to 2014 at the Moghan Meteorological Research Farm and agricultural data from 51 synoptic stations in the northwest of the country (1996-2016) selected from the General Meteorological Organization of the Country have been used. To carry out this research, thermal requirements in each of the 5 main phases of phenology have been determined at the Moghan station, then using the regression equation between the 15-day average of temperature and altitude, a temperature-temperature history map for seed cultivation in all stations from the first half of the year was drawn using Geographic Information System software. Also, the length of scientific periods and the degree of growth day were calculated and the relevant maps were drawn using the Kriging method. Then, it was combined with the layers of altitude, slope of the region and land use, and finally, a zoning map of lands suitable for grain corn cultivation in the northwest of the country was drawn. Based on the results obtained, 27.6 percent of the study area is capable of cultivating this plant.